Tourism Development and Strategy for Increasing Numbers of Visitors in Kediri - Azizah, Anisah (Journal of Indonesian Tourism and Development Studies, 2017)
Tourism is one source of local revenue. The key to improve quality of tourism destination is effective strategy to develop tourism sectors. To develop tourism sector, one should emphasize on adequate maintenance of tourism destination and management. Studies have been conducted in Kediri analyzing how potential the area was for tourism destination. It was expected that number of visitors and local revenue would increase by describing both internal and external factors supporting the tourism sector in the area. The study was a descriptive study that employed mixed methods (quantitative and qualitative). The data analysis methods were SWOT analysis followed by weighing using IFAS-EFAS analysis. The findings were (a) the government of Kediri should build shopping center that highlighted the local wisdom and more shopping centers more particularly in tourist destination that had no "something to buy" yet, (b) launch various tourism programs, (c) spread information about tourism in Kediri more widely, and (d) involve various types of mass media for promoting the tourism spots in Kediri. It was predicted that the strategy of which purpose was improving quality of tourism spot along with the continuous development plan would improve tourism sector in the area. Once targeted number of visitors had been achieved, the local revenue of Kediri would increase simultaneously. Recommendation strategy is Aggressive Maintenance strategy, where institutions or organizations responsible for the tourism destination develop the area actively and aggressively. We recommend the procedures of the Aggressive Maintenance to develop logic and analytical concepts, as well as make analysis and conceptualize short and long-term priorities. Keywords: Kediri, SWOT, Tourism Development.